2020
DOI: 10.1161/jaha.119.012199
|View full text |Cite|
|
Sign up to set email alerts
|

Regional Variation of Mortality in Heart Failure With Reduced and Preserved Ejection Fraction Across Asia: Outcomes in the ASIAN‐HF Registry

Abstract: Background Data comparing outcomes in heart failure ( HF ) across Asia are limited. We examined regional variation in mortality among patients with HF enrolled in the ASIAN ‐HF (Asian Sudden Cardiac Death in Heart Failure) registry with separate analyses for those with reduced ejection fraction ( EF ; <40%) versus preserved EF (≥50%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 19 publications
8
59
4
Order By: Relevance
“…In Asia, data from the ASIAN-HF registry showed a 1-year all-cause mortality of 13% for patients with either HFpEF or HFrEF enrolled as in-patients. 24 Patients with acute heart failure enrolled in the Trivandrum Heart Failure Registry 25 southeast Asia (23%), and China (17%) were consistent with or exceeded those reported for patients enrolled in hospital in INTER-CHF. 4 We suggest that any differences in mortality in other registries and those in REPORT-HF might be due to differences in centres included, proportion of patients dwelling in rural areas, and the need for patients to consent to partici pation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In Asia, data from the ASIAN-HF registry showed a 1-year all-cause mortality of 13% for patients with either HFpEF or HFrEF enrolled as in-patients. 24 Patients with acute heart failure enrolled in the Trivandrum Heart Failure Registry 25 southeast Asia (23%), and China (17%) were consistent with or exceeded those reported for patients enrolled in hospital in INTER-CHF. 4 We suggest that any differences in mortality in other registries and those in REPORT-HF might be due to differences in centres included, proportion of patients dwelling in rural areas, and the need for patients to consent to partici pation.…”
Section: Discussionsupporting
confidence: 56%
“…Over [22][23][24][25][26][27] vs 28 [24][25][26][27][28][29][30][31][32][33][34]) and were more often admitted with a first episode of heart failure. Despite their relative youth, patients from lower-middle-income countries were in a worse (ie, higher) New York Heart Association class class, more often had HFrEF, and generally had worse signs and symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the existence of evidence-based and well-established national guidelines, PP ICD implant rates vary among countries and are low in Asian countries. 17 29 Previous studies reported that PP ICD implantation rates for eligible patients were 10%, 60%, and 5% in Sweden, US, and an Asian country, respectively. 25 26 29 The present study showed that only 5.23% of patients who were eligible for PP ICD were treated with ICDs.…”
Section: Discussionmentioning
confidence: 99%
“…17 29 Previous studies reported that PP ICD implantation rates for eligible patients were 10%, 60%, and 5% in Sweden, US, and an Asian country, respectively. 25 26 29 The present study showed that only 5.23% of patients who were eligible for PP ICD were treated with ICDs. We could not evaluate whether electrophysiology study was performed in patients whose LVEF was over 35% according to guidelines because of the multicenter study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation